Deep Brain Stimulation of the Subthalamic Nucleus Induces Impulsive Responses to Bursts of Sensory Evidence - London, Dennis; Pourfar, Michael H.; Mogilner, Alon Y. (Frontiers in Neuroscience, 2019)
Decisions are made through the integration of external and internal inputs until a threshold is reached, triggering a response. The subthalamic nucleus (STN) has been implicated in adjusting the decision bound to prevent impulsivity during difficult decisions. We combine model-based and model-free approaches to test the theory that the STN raises the decision bound, a process impaired by deep brain stimulation (DBS). 8 male and female human subjects receiving treatment for Parkinson's disease with bilateral DBS of the STN performed an auditory two-alternative forced choice task. By ending trials unpredictably, we collected reaction time (RT) trials in which subjects reached their decision bound and non-RT trials in which subjects were forced to make a decision with less evidence. A decreased decision bound would cause worse performance on RT trials, and we found this to be the case on left-sided RT trials. Drift diffusion modeling showed a negative drift rate. This implies that in the absence of new evidence, the amount of evidence accumulated tends to drift toward zero. If evidence is accumulated at a constant rate this results in the evidence accumulated reaching an asymptote, the distance of which from the bound was decreased by DBS (p=0.0079, random shuffle test), preventing subjects from controlling impulsivity. Subjects were more impulsive to bursts of stimuli associated with conflict (p<0.001, cluster mass test). In addition, DBS lowered the decision bound specifically after error trials, decreasing the probability of switching to a non-RT trial after an error compared to correct response (28% vs 38%, p=0.005, Fisher exact test). The STN appears to function in decision-making by modulating the decision bound and drift rate to allow the suppression of impulsive responses.